The Influence Of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan To Deposit Ratio (LDR), And Operational Costs To Operating Income (BOPO) On Return On Asset (ROA) In Banks Listed On The Indonesia Stock Exchange - Adhim, Chairul; Mulyati, Mulyati (Publisher Cv. Inara, 2024)
The objective of this research is to determine the effect of the Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operational Costs to Operating Income (BOPO) on Return on Assets (ROA) in banks listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, with a total of 32 banks. The research data were tested using multiple regression analysis. The results of the study show that the Capital Adequacy Ratio (CAR) has no effect on Return on Assets (ROA), while Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operational Costs to Operating Income (BOPO) have a negative and significant effect on Return on Assets (ROA). y.